for Developing Lexical Competence of Non-Philological Methodology University Students in the Context of Digital Technologies (Journal of Science-Innovative Research in Uzbekistan, 2025)
The integration of digital technologies into higher education has created innovative pathways for enhancing linguistic abilities. This article explores methodological approaches to developing lexical competence among non-philological university students, emphasizing the role of digital tools in promoting vocabulary acquisition, contextual usage, and autonomous learning. The study evaluates educational platforms, gamified apps, and mobile-assisted language learning environments. Findings demonstrate that technology-enhanced lexical instruction significantly improves retention, motivation, and overall language proficiency.